The experience of first-time parents in the transition to parenthood: Scoping review - Machfudloh, Machfudloh; Astuti, Andari Wuri; Suryaningsih, Endang Koni (Journal of Health Technology Assessment in Midwifery, 2023)
Background: Marriage is everyone's dream and need to create a whole and happy family (household). Changing the status and role of being a parent is fun and even sad if the adjustment is not properly prepared. Self-acceptance as a parent can affect a person's psychological level where the rates of stress, depression, violence against family children, and even divorce experience an increasing trend. Young parents are more vulnerable to becoming victims of both physical and verbal violence. Methods: The method in this research is scoping review. The literature search in this study used three medical journal databases, namely Ebsco, ProQuest, and Willey Online Library, and one search engine, namely Google Scholar. Articles were selected using inclusion criteria, namely original research, in English and Indonesian, published within the last 5 years (2017-2022). The total search results were 3,395 articles. 10 articles that met the inclusion criteria in the authors' review were found. The instrument used to assess the quality of articles was the Joana Briggs tool from the Joana Briggs Institute (JBI). Conclusion: From the results of the review, it was found three themes related to readiness, influencing factors, and support in the transition to parenthood. The review of the ten articles showed that the transition to parenthood requires readiness both physically and mentally, internal and external factors, and the need for support from family, social, and health services.